2021
DOI: 10.1016/j.fertnstert.2020.07.053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different sources of platelet-rich plasma as treatment option for infertility-causing endometrial pathologies

Abstract: Objective. To study the effect of human plasma from different sources such as 2 umbilical cord blood and adult blood platelet-rich plasma (PRP) on the 3 regeneration of endometrial damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 43 publications
1
36
0
1
Order By: Relevance
“…PRP-treated ovaries had significantly more pre-antral and antral follicles up to 30 days after treatment, suggesting that PRP may be a viable option for driving folliculogenesis in females with PCOS. In addition, platelets also release significant quantities of IL-15 when activated ( de Miguel-Gómez et al, 2020 ). Increased IL-15 concentrations in follicular fluid have been negatively correlated with pregnancy outcomes via IVF, indicating that this cytokine may be detrimental to follicle maturation ( Spanou et al , 2018 ).…”
Section: Prp: a Note Of Cautionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRP-treated ovaries had significantly more pre-antral and antral follicles up to 30 days after treatment, suggesting that PRP may be a viable option for driving folliculogenesis in females with PCOS. In addition, platelets also release significant quantities of IL-15 when activated ( de Miguel-Gómez et al, 2020 ). Increased IL-15 concentrations in follicular fluid have been negatively correlated with pregnancy outcomes via IVF, indicating that this cytokine may be detrimental to follicle maturation ( Spanou et al , 2018 ).…”
Section: Prp: a Note Of Cautionmentioning
confidence: 99%
“…Even though there are other biological derivatives, such as human umbilical cord plasma, which may provide additional benefits in the sphere of ART ( de Miguel-Gómez et al, 2020 ), the appeal of PRP lies in its balance among therapeutic effect, cost effectiveness, ease of isolation and autologous nature. However, with the increased interest of ovarian PRP injection inconclusive efficacy and lack of understanding of mechanism of action, fundamental research into the effect of this therapy on the cellular level is required.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…ucPRP is derived from naive umbilical cord tissue, has a wide range of sources and more abundant growth factors than peripheral blood, and is a safe and effective substitute for patients with contraindications to autologous PRP [ 20 , 39 ]. A recent clinical study showed that ucPRP has a better effect than peripheral blood PRP for the treatment of endometrial injury infertility [ 40 ]. However, the beneficial effects of combined transplantation of HucMSCs and ucPRP in POF rats have not been discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, subsequent IUA management is considered necessary when IUA occurs. Thus far, there have been many publications addressing the topic of the management of IUA [ 23 , 24 , 26 , 27 , 28 , 29 , 30 , 35 , 40 , 43 , 57 , 58 , 59 , 62 , 64 , 131 , 132 , 133 , 134 , 135 , 136 , 138 , 139 , 140 , 141 , 142 , 155 , 164 , 165 , 166 , 167 , 168 ].…”
Section: Future Vision Of Iua Managementmentioning
confidence: 99%